When NIPT meets WES, prenatal diagnosticians face the dilemma: genetic etiological analysis of 2,328 cases of NT thickening and follow-up of pregnancy outcomes - Ji, Xueqi; Li, Qiongmei; Qi, Yiming; Wang, Xingwang; Ding, Hongke; Lu, Jian; Zhang, Yan; Yin, Aihua (Frontiers in Genetics, 2023)
Objective To assess the performance of diverse prenatal diagnostic approaches for nuchal translucency(NT) thickening and to investigate the optimal prenatal screening or diagnostic action with NT 95th percentile-3.50 mm. Methods A retrospective analysis of 2328 pregnancies with NT ≥95th percentile through ultrasound-guided trans abdominal chorionic villus sampling (CVS), amniocentesis, or cordocentesis obtained clinical samples (chorionic villi, amniotic fluid, and cord blood), and real-time quantitative fluorescent PCR (QF-PCR), chromosome karyotyping (CS), chromosome microarray analysis (CMA), or whole exome sequencing (WES) was provided to identify genetic etiological. Results In this study, the incidence of chromosomal defects increases with NT thickness. When NT ≥6.5 mm, 71.43% were attributed to genetic abnormalities. The 994 gravidas with fetal NT thickening finished STR, CS，and CMA. In 804 fetuses with normal karyotypes, CMA detected 16 (1.99% ) extra pathogenic or likely pathogenic copy number variations (CNVs). The incremental yield of CMA was only 1.16% (3/229) and 3.37% (10/297) in the group with NT 95th percentile-2.99 mm and NT 3.0-3.49 mm, separately. Among 525 gravidas with fetal NT thickening finished STR, CMA, and WES, the incremental yield of WES was 4.09% (21/513). In the group of NT 95th percentile-2.99 mm, there was no additional single-nucleotide variations (SNVs) were detected in WES, while in 143 cases with NT 3.0-3.49 mm, the incremental yield of WES was 5.59% (8/143). Conclusion In the group of NT 95th percentile-3.0 mm, since chromosomal aneuploidy and chromosomal copy number variation are the primary causes and the additional contribution of CMA and WES is not significant, we recommend NIPT-Plus for pregnant women with NT thickening of 95th percentile-3.0 mm first. In addition, comprehensive prenatal genetic testing involving CMA and WES can benefit pregnancies with NT thickening of 3.0-3.49 mm.